PENGARUH MANAJEMEN INOVASI DAN BERBAGI PENGETAHUAN TERHADAP KEUNGGULAN KOMPETITIF PADA INDUSTRI MANUFAKTUR BATAM - Alfa, Tomi; Mustofa, Amirul; Yunus, Eddy (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study investigates the impact of innovation management and knowledge sharing on competitive advantage within Batam’s manufacturing industry. In an era of rapid globalization and technological transformation, innovation and effective knowledge management are critical to achieving a competitive edge. The research employs a quantitative approach, using surveys to collect data from manufacturing firms in Batam, which is analyzed using multiple linear regression techniques. The findings demonstrate that both innovation management and knowledge sharing have a significant positive influence on competitive advantage. The study emphasizes the importance of fostering an organizational culture conducive to learning, cross-functional collaboration, and leveraging information technology to support innovation processes. This research offers practical recommendations for industry managers to develop sustainable innovation strategies and knowledge-sharing practices, ultimately boosting their firms' competitiveness.